ANALISIS QUESTIONING SKILL GURU SDN 4 KANDANGREJO PADA MATA PELAJARAN IPAS KELAS IV - Meilisya Ulya Putri Pratama; Erik Aditia Ismaya; Sekar Dwi Ardianti (Jurnal Ilmiah Bina Edukasi, 2025)
This study aims to describe the questioning skills of elementary school teachers in the subject of Social Sciences and students' responses to teachers' questioning skills. This research was conducted at SDN 4 Kandangrejo. The implementation time is carried out when social studies subjects are ongoing. The data source of this study is grade IV teachers and 6 grade IV students with student ability categories, namely high, medium, and low. This study uses a qualitative approach with a case study method. The data collection techniques used by the researcher are observation, anecdotal notes, interviews and documentation. The validity of the data was tested by the method of triangulation of sources, techniques, time, and member checks. The research instruments used were interview sheets, anecdotal notes, and observation sheets. The data analysis used in this study is data collection, data reduction, data presentation, verification (drawing conclusions). The results of this study can show that: a.) The teacher's questioning skills can be categorized as good with a score of 129 out of 176. b.) Students' responses to the teacher's questioning skills showed significant variations